Penatalaksanaan Fisioterapi Pada Kasus Post Orif Fracture 1/3 Distal Os Radius Sinistra Di RSUD Panembahan Senopati Bantul - Renjana, M. Banjaransari Yan; , Totok Budi Santoso S.Fis , MPH (2016)
Background : Fracture is a break bones contuinitas determined according to the type and extent, fracture occurs when the bones are subject to greater stress than to diabsorbsinya, In the case can be dealt with interventiom from docter, medikamentosa, nutritionist, physiotherapy, and other . Physiotherapy in these cases can reduce pain improve range of motion, increase muscle strength using modalities Infrared (IR) and the hold-relax exercise therapy Objective : To investigate the implementation of physiotherapy in reducing pain, increasing range of motion and increase muscle strength in the case of post ORIF os distal 1/3 radius of the left using the modality using Infrared and exercise therapy modality hold relax Result : After terapy for about four times the obtained results of the assessment of pain in painful,pain silence T1 : 0 to be T4:0 , painful press T1: 1,8 cm to be T4:1,2 cm , motion painful T1:4,8 cm to be T4:4,0 cm. Increase range of motion wrist joint S:T1 : 10º-0º-30º become S: T4: 15º-0º-35º, F:T1: 7º-0º-10º become F : T4: 13º-0º-20º. Increase muscle of wrist joint , wrist flexor T1 : 3 become T4 : 4, ekstensor wrist T1:3 become T4 : 4, radial deviator T1 : 3 become T4 : 3, ulna deviator T1 become T4 : 3 Conclusion: Infrared and Hold Relax exercise therapy can reduce pain,can increase the range of motion in his left hand in the condition and can increase muscle strength.